Introductory Overview - Melinda Coetzee; Dries Schreuder (SA Journal of Human Resource Management, 2005)
This edition is about mentoring in the South African organisational context. Although extensive literature exists on the topic of mentoring, the current state of mentoring in the South African organisational context is under-researched and not yet well explored, particularly in the context of employment equity. This special edition on mentoring therefore aims to provide an overview of current research, practices and experiences regarding mentoring in the multi-cultural South African organisational context.